1977
DOI: 10.1302/0301-620x.59b2.873982
|View full text |Cite
|
Sign up to set email alerts
|

Chondrosarcoma of the bones of the hand

Abstract: Nineteen chondrosarcomas are reported arising in proximal phalanges or metacarpal bones of the hand mainly in elderly patients, predominantly women. The usual clinical presentation was of a progressively painful large tumour, often arising in a dormant lesion near the metacarpo-phalangeal joint. Radiologically most showed some bone expansion with a poorly defined area of destruction and a considerable soft-tissue swelling. Histologically, malignancy was usually obvious, but confusion might arise from the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
5

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 5 publications
1
27
0
5
Order By: Relevance
“…The main symptom is progressive swelling, generallyassociated with pain [16] (Figure 2(a)). Many patients have symptoms for several years before being visited by a surgeon.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The main symptom is progressive swelling, generallyassociated with pain [16] (Figure 2(a)). Many patients have symptoms for several years before being visited by a surgeon.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…The main differential diagnosis is enchondroma; other possibilities are: ganglion, bursa, gout, rheumatoid arthritis, cyst, onychomatricoma and chondromyxoid fibroma (very rare in the hands) [16]. From a clinical point of view enchondroma could be easily distinguished from CS because the former rarely causes pain or swelling, except in case of fractures.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…When comparing data with international reports, the age range was nearly equal to several studies that the neo-plasm has a wide age range, but most of the patients are in the second and third decades of life [14] and [7,23] who reported that Patients are usually between ages 20 and 40 years. In contrast to other studies that showed CS has a high incidence between the fourth and sixth decades of life [23][24][25], while others described that the majority of patients affected are over 50 years old [2,26]. However, Differences a cross epidemiological studies conducted in different parts of the world in incidence and frequency of age by decade of patients affected by CS may somewhat reflect or a representative of genetic background or a largely unknown risk factors.…”
Section: Discussionmentioning
confidence: 80%
“…These forms of chondromatosis are associated with somatic mutation in Isocitrate Dehydrogenase 1 (IDH1) gene and isocitrate dehydrogenase 2 (IDH2) gene [27]. Furthermore, the main symptom of CS is progressive swelling, generally associated with pain [24]. Many patients have symptoms for several years before being visited by a surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Chondrosarcoma is often separated into three histological grades: low (Grade 1), medium (Grade 2) and high (Grade 3). [3] The higher the grade, the more likely it is that the tumour will metastasise.…”
Section: Histology Macroscopic Appearancementioning
confidence: 99%